Discussing treatment burden. Issue 1 (March 2021) - Powell, Pippa; Saggu, Ravijyot; Jones, Steve; Clari, Marco; Saraiva, Isabel; Hardavella, Georgia; Hansen, Kjeld; Pinnock, Hilary
Treatment burden is defined as "the workload of healthcare and its effect on patient functioning and well-being" [1, 2]. It has also been defined as "the self-care practices that patients with chronic illness must perform to respond to the requirements of their healthcare providers, as well as the impact that these practices have on patient functioning and well-being" [3]. In this issue of Breathe, there are several articles addressing treatment burden from different perspectives. This Viewpoint article focusses on the discussions between the patient and their healthcare professional (HCP). What are the important topics to cover in discussions about treatment burden? What are the barriers to these discussions? What facilitates a productive conversation about treatment burden? The authors of this article include three patients (with asthma, COPD and idiopathic pulmonary fibrosis (IPF), four HCPs representing different specialties (primary care, secondary and tertiary care, nursing and pharmacy) and a representative of the European Lung Foundation (ELF). This article is based on a video discussion between the authors; it was then refined via e-mail by all the authors. Healthcare professionals should help patients to reach informed decisions about treatments in order to maximise benefits while minimising treatment burden https://bit.ly/2XRtRPK